The British Labour Movement and Imperialism. - Frank, Billy (Historian) (Cambridge Scholars Pub., 2010)
This edited collection explores the British labour movement's relationship with imperialism in the period 1800-1982 through nine inter-connected articles. Labour historians have tended to neglect the labour movement's interaction with imperialism, preferr.